First Draft Assembly and Annotation of the Genome of a California Endemic Oak Quercus lobata Née (Fagaceae). Issue 11 (1st November 2016) - Sork, Victoria L; Fitz-Gibbon, Sorel T; Puiu, Daniela; Crepeau, Marc; Gugger, Paul F; Sherman, Rachel; Stevens, Kristian; Langley, Charles H; Pellegrini, Matteo; Salzberg, Steven L
Abstract: Oak represents a valuable natural resource across Northern Hemisphere ecosystems, attracting a large research community studying its genetics, ecology, conservation, and management. Here we introduce a draft genome assembly of valley oak ( Quercus lobata ) using Illumina sequencing of adult leaf tissue of a tree found in an accessible, well-studied, natural southern California population. Our assembly includes a nuclear genome and a complete chloroplast genome, along with annotation of encoded genes. The assembly contains 94, 394 scaffolds, totaling 1.17 Gb with 18, 512 scaffolds of length 2 kb or longer, with a total length of 1.15 Gb, and a N50 scaffold size of 278, 077 kb. The k -mer histograms indicate an diploid genome size of ∼720–730 Mb, which is smaller than the total length due to high heterozygosity, estimated at 1.25%. A comparison with a recently published European oak ( Q. robur ) nuclear sequence indicates 93% similarity. The Q. lobata chloroplast genome has 99% identity with another North American oak, Q. rubra . Preliminary annotation yielded an estimate of 61, 773 predicted protein-coding genes, of which 71% had similarity to known protein domains. We searched 956 Benchmarking Universal Single-Copy Orthologs, and found 863 complete orthologs, of which 450 were present in > 1 copy. We also examined an earlier version (v0.5) where duplicate haplotypes were removed to discover variants. These additional sources indicate that the predicted gene count in Version 1.0 is overestimated by 37–52%. Nonetheless, this first draft valley oak genome assembly represents a high-quality, well-annotated genome that provides a tool for forest restoration and management practices.